1986
DOI: 10.1530/jrf.0.0770537
|View full text |Cite
|
Sign up to set email alerts
|

The concerted effect of  -chlorohydrin and glucose on the ATP concentration in spermatozoa is associated with the accumulation of glycolytic intermediates

Abstract: Summary. In the absence of a glycolysable sugar the effect of 1 mM-RS-\g=a\-chlorohydrin on the ATP concentration in ram or boar spermatozoa was relatively small but the addition of 0\m=.\10or 0\m=.\03 mM-glucose initiated a rapid loss of ATP. When the spermatoza were incubated with 0\m=.\05mM-RS-\g=a\-chlorohydrin, the addition of 1\m=.\0mM (ram) or 0\m=.\06mM (boar)-glucose was required to produce ATP dissipation. In ram spermatozoa treated with 0\m=.\05or 1\m=.\00mM-RS-\g=a\-chlorohydrin, ATP loss was cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
5
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 10 publications
(9 reference statements)
5
5
0
Order By: Relevance
“…When BHB was supplemented to the sperm suspension instead of glucose, the percentage of sperm motility was not affected by α-chlorohydrin (ACH), a potent inhibitor of GAPDH. Moreover, it was reported that intracellular ATP concentration was not decreased by ACH in the absence of glucose (Ford and Harrison, 1985;Ford and Harrison, 1986). These results support that respiration is enough to supply ATP for sperm motility.…”
Section: Introductionsupporting
confidence: 63%
“…When BHB was supplemented to the sperm suspension instead of glucose, the percentage of sperm motility was not affected by α-chlorohydrin (ACH), a potent inhibitor of GAPDH. Moreover, it was reported that intracellular ATP concentration was not decreased by ACH in the absence of glucose (Ford and Harrison, 1985;Ford and Harrison, 1986). These results support that respiration is enough to supply ATP for sperm motility.…”
Section: Introductionsupporting
confidence: 63%
“…Previous studies have shown ACH affected sperm GAPDS activity or ATP levels [22], [58][59]. In this study, on only GAPDS activity and ATP levels, but also cAMP levels, P-PKAs and PTP significantly decreased while rat sperm were exposed to SACH.…”
Section: Discussionsupporting
confidence: 44%
“…Incubations. These were done in 10-ml conical flasks in a shaking water bath at 34°C with air as the gas phase and were organized in a similar way to previous experiments (Ford et ai, 1981;Ford & Harrison, 1986). The incubation period with a-chlorohydrin before the addition of substate was 10 min for boar and 30 min for rat spermatozoa.…”
Section: Methodsmentioning
confidence: 99%
“…Under a variety ofconditions the decrease in ATP was always accompanied by a concomitant increase in the concentration of fructose 1,6-bisphosphate. Fructose 1,6-bisphosphate never accumulated when there was no decline in ATP (Ford & Harrison, 1986).…”
Section: Introductionmentioning
confidence: 94%